2023
DOI: 10.1002/jmor.21621
|View full text |Cite
|
Sign up to set email alerts
|

Nasal turbinates of the dicynodont Kawingasaurus fossilis and the possible impact of the fossorial habitat on the evolution of endothermy

Michael Laaß,
Anders Kaestner

Abstract: The nasal region of the fossorial anomodont Kawingasaurus fossilis was virtually reconstructed from neutron‐computed tomographic data and compared with the terrestrial species Pristerodon mackayi and other nonmammalian synapsids. The tomography of the Kawingasaurus skull reveals a pattern of maxillo‐, naso‐, fronto‐ and ethmoturbinal ridges that strongly resemble the mammalian condition. On both sides of the nasal cavity, remains of scrolled maxilloturbinals were preserved that were still partially articulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 176 publications
(489 reference statements)
1
12
0
Order By: Relevance
“…All these structures are identified as for blood vessels or nerves 81 . Ruf et al 29 and Laaß and Kaestner 40 identified this groove as for the olfactory nerve; however, Angielczyk et al 85 interpreted it as the ophthalmic canals of the trigeminal nerve. Due to the grooves formed by the ethmoidal and lateral ridges are divided into branches anteriorly that end in the posterior border of the external nares would support the hypothesis that these grooves housed the olfactory nerve, as proposed by others 29 , 40 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…All these structures are identified as for blood vessels or nerves 81 . Ruf et al 29 and Laaß and Kaestner 40 identified this groove as for the olfactory nerve; however, Angielczyk et al 85 interpreted it as the ophthalmic canals of the trigeminal nerve. Due to the grooves formed by the ethmoidal and lateral ridges are divided into branches anteriorly that end in the posterior border of the external nares would support the hypothesis that these grooves housed the olfactory nerve, as proposed by others 29 , 40 .…”
Section: Discussionmentioning
confidence: 99%
“…If turbinals were present in extinct groups of synapsids, such as “pelycosaurs”, therocephalians, non-mammaliaform cynodonts 19 , 27 39 , they remained cartilaginous 19 (but see 40 ); therefore, they are hardly preserved in the fossil record. Despite this, other structures can prove indirectly the presence of these cartilaginous tissues inside the nasal cavity of non-mammaliaform synapsids 19 , 28 , 29 , 31 , 33 .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations